On nonuniform traffic pattern of modified hierarchical 3D-torus network - Rahman, M.M. Hafizur; Sato, Yukinori; Inoguchi, Yasushi (Denshi Jouhou Tsuushin Gakkai, 2011)
A Modified Hierarchical 3D-Torus (MH3DT) network is a 3D-torus network consists of multiple basic modules, in which each basic module itself is a 3D-torus network. Dynamic communication performance has been evaluated using dimension-order routing and $2$ virtual channels (VCs) under uniform traffic patterns but not under non-uniform traffic patterns. In this paper, we evaluate the dynamic communication performance of MH3DT under five non-uniform traffic patterns, and compare it with other networks. We found that under non-uniform traffic patterns, the MH3DT yields high throughput and low latency, providing better dynamic communication performance compared to H3DT, TESH, mesh, and torus networks. Also, we found that non-uniform traffic patterns have higher throughput than uniform traffic patterns in the MH3DT network.